The crystal structure of 3-(1′-deoxy-3′,5′-O-dibenzy-β-d-ribosyl)adenine dichloromethane solvate, C49H52Cl2N10O6 - Wang Pingqiao; Zhu Yunlong; Ding Haixin; Huang Haiyang (Zeitschrift für Kristallographie - New Crystal Structures)
C49H52Cl2N10O6, monoclinic, P21 (no. 4), a = 12.2875(14) Å, b = 8.3031(10) Å, c = 13.1242(15) Å, β = 100.0640(10)∘ $100.0640{(10)}^{° }$ , V = 1318.4(3) Å3, Z = 1, Rgt ${R}_{gt}$ (F) = 0.0736, wRref $wR_{ref}$ (F 2) = 0.1545, T = 296 K.